Bending strain tolerance of MgB2 superconducting wires. (22nd February 2016) - Kováč, P; Hušek, I; Melišek, T; Kulich, M; Kopera, L
Abstract: This work describes the strain tolerance of MgB2 superconductors subjected to variable bending stresses. Bending of MgB2 wire was done at room temperature in different modes: (i) direct bending of straight annealed samples to variable diameters and by (ii) indirect bending by straightening of bent and annealed samples. I c –bending strain characteristics of samples made by in situ PIT and by the internal magnesium diffusion (IMD) process were measured at 4.2 K. The results show a good agreement between the direct and indirect bending mode, which allows easier estimation of limits important for the winding process of MgB2 superconductors with brittle filaments. A comparison of MgB2 wires made by in situ PIT and IMD processes showed improved strain tolerance for IMD due to better grain connectivity the low annealing temperature, which does not appear to reduce the mechanical strength of sheath material.